Features of B cell subsets in primary Sjogren’s syndrome and systemic lupus erythematosus - S. S. Benevolenskaya; I. V. Kudriavtsev; M. K. Serebriakova; I. N. Grigor’yeva; E. S. Kuvardin; A. I. Budkova; S. V. Koniakhin; D. B. Zammoeva; D. B. Motorin; A. Yu. Zaritskey; I. Z. Gaydukova; E. K. Gaydukova; et al. (Научно-практическая ревматология)
Background. Lymphocyte subsets in autoimmune diseases, such as systemic lupus erythematosus (SLE) and primary Sjogren’s syndrome (pSS), have been intensively studied in recent years. However, their clinical and diagnostic significance has not been finally determined.The aim of the study – to investigate features and diagnostic utility of B cell subcets in systemic lupus erythematosus and primary Sjogren’s syndrome.Material and methods. A total of 27 SLE patients, 41 pSS patients and 49 healthy volunteers were included in the study. Phenotyping of blood B cell subpopulations was carried out by means of flow cytometry. All peripheral blood B cells were identified by using CD19 antibody, detection of subpopulations of B cells based on expression of IgD, CD38, CD27. Statistical analysis was carried out using Statistica v. 12.0 (StatSoft Inc., USA). The absolute and relative values of B lymphocyte subpopulations were evaluated using three main classifications: based on IgD and CD38 co-expression, IgD and CD27 co-expression as well as CD38 and CD27 co-expression. For comparison of quantitative traits, the Mann – Whitney U-test and Kruskal – Wallis test were used. Method of discriminant analysis was performed to evaluate diagnostic utility of B cell subsets.Results. The most significant discriminant model was obtained using the relative values of all subpopulations.In this model the top significance was documented while assessing the percentage of «unswitched» memory В-cells (IgDdimCD27dim), «naive» (IgDdimCD38low) and activated «naive» B cells (IgDdimCD38dim), germinal center progenitor B cells (IgDhiCD38hi), germinal center B cells (IgDdimCD38hi) and «transient» B cells (CD27lowCD38hi), model percent correct was 75.2% (p<0.05). During ROC analysis, performed for the differential diagnosis of healthy and sick patients, this discriminant model had a sensitivity of 70.6% and a specificity of 85.7%, the area under the curve (AUC) – 0.91 (p<0.001). Among the group of ill patients, distinguishing between SLE and pSS showed a sensitivity of 81.5% and а specificity of 80.5%, AUC=0.84 (p<0.001).Conclusion. B cell subsets might provide an additional diagnostic tool to differentiate between SLE and pSS.